Management by ROI as a Source of Competitive Advantage for Organizations - Filip REBETAK; Viera BARTOSOVA (Communications of International Proceedings, 2021)
At present, the position of the organization's financial management, its tasks and the content of its activities are significantly changing. It must seek and find answers to economic events in a market economy environment, and thus achieve fundamental changes in the performance of the organization. The main capital of organizations in a rapidly changing market environment is the latest knowledge and managers who are well prepared for economic events in the new conditions of dynamic development of the globalization of the economy. They must be able to respond correctly to the movements of the macroeconomic and microeconomic environment. New management methods, such as management by ROI (return on investment), do not reject previous concepts in organizations and the management of processes and their resources, on the contrary, they require their maximum knowledge, because they draw from them and combine what is appropriate in a particular situation and beneficial to the organization. However, the concepts developed in the past for individual areas of financial management, process and resource management did not end either the development of concepts or the development of techniques within concepts. It is therefore necessary to constantly monitor new, emerging concepts and techniques and use their results. The development of organizational and management concepts and their techniques within the company can also be a significant benefit, because this is what creates the company's unique competitive advantages. In this article, we focus on the management by ROI as a new method to improve organizational performance in line with the interest of its stakeholders.
Keywords: Financial Management; Management By Objectives; Management By ROI; Return On Investment